Array : AN EXPRESSION OF FEAR OF MISSING OUT OF TREND TIKTOK - haryono, putri ameilia; M.Si, Dr. Setyo Yanuartuti (Solah, 2023)
Fomo On TikTok dance work is a work that describes a person's feelings of fear if they are left behind by a current trend. This work departs from the phenomenon of Fear Of Missing Out which is interpreted in Indonesian, namely fear of being left behind. The focus of this work is about the fear of being left behind by trends on the TikTok application that can cause anxiety. The focus of the form in this work is the dramatic dance type form. Dramatic dance type forms that will be related to construction method 1, including initial stimulation, determination of dance type, determination of presentation mode, improvisation, evaluation, selection and refinement, and finally motifs. The feeling of fear of being left behind towards the TikTok trend is expressed through the properties of ringlight and klewer cloth which is then removed describing such as the fear of being left behind The feeling of being left behind towards the TikTok trend is also expressed verbally through accompaniment music, creator content sentences and even TikTok movements that are verbally included in this work.